2001
DOI: 10.1046/j.1365-2346.2001.00891.x
|View full text |Cite
|
Sign up to set email alerts
|

Do patient information booklets increase perioperative anxiety?

Abstract: Patient attitudes to medical information are changing. We audited patient attitudes to an information leaflet provided at the preadmission clinic as part of standard day-case protocol. The booklet is a simplified version of the booklet Anaesthesia and Anaesthetists--Information for Patients and Relatives published in London, UK, by the Association of Anaesthetists of Great Britain & Ireland. One hundred and three patients were surveyed before surgery over a 2-month period using an anonymous questionnaire. Of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
0
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 8 publications
(12 reference statements)
0
27
0
4
Order By: Relevance
“…For example, the anaesthetist explaining events and being given prior notice of proceedings (sequential order of events) were beneficial in that it helped to reduce anxiety (Table 3). Other studies have likewise revealed such information and choice to be crucial in modern elective surgery (McKenna 1997, Ward et al 2007, Gillies and Baldwin 2001. However, debate frequently occurs regarding the ideal time for the anaesthetist to visit patients to impart such information.…”
Section: N T R a -O P E R A T I V E I N T E R V E N T I O Nmentioning
confidence: 99%
“…For example, the anaesthetist explaining events and being given prior notice of proceedings (sequential order of events) were beneficial in that it helped to reduce anxiety (Table 3). Other studies have likewise revealed such information and choice to be crucial in modern elective surgery (McKenna 1997, Ward et al 2007, Gillies and Baldwin 2001. However, debate frequently occurs regarding the ideal time for the anaesthetist to visit patients to impart such information.…”
Section: N T R a -O P E R A T I V E I N T E R V E N T I O Nmentioning
confidence: 99%
“…It has been documented that, in addition to simple drawings and shapes, giving images of surgical intervention and anaesthesia processes via informative leaflets or multimedia means like CD and DVD to the patients does not increase the uneasiness of the patients and actually contributes to the operation being better understood (25,26).…”
Section: How Should We Increase the Rate Of Reading Icd?mentioning
confidence: 99%
“…An attempt to understand why chronic b-blockade is potentially beneficial in cardiac surgery [1,2] and not in noncardiac surgery [3][4][5][6][7][8], may help identify factors associated with an improved peri-operative outcome in chronically b-blocked patients. While patients undergoing non-cardiac surgery were more likely to be b-blocked for angina and hypertension and die of ischaemicrelated causes in the peri-operative period [3], a larger proportion of the cardiac surgery patients had heart failure [1] and were more likely to die of heart failure than of ischaemic causes [2].…”
mentioning
confidence: 99%
“…While patients undergoing non-cardiac surgery were more likely to be b-blocked for angina and hypertension and die of ischaemicrelated causes in the peri-operative period [3], a larger proportion of the cardiac surgery patients had heart failure [1] and were more likely to die of heart failure than of ischaemic causes [2]. Thus, chronic b-blockade in patients with angina or hypertension without severe myocardial dysfunction may not alter peri-operative outcome [3]. Indeed, the lowering of the ischaemic threshold [9] is potentially detrimental and 'clamping the heart rate' may be desirable.…”
mentioning
confidence: 99%
See 1 more Smart Citation